تحليل أداء وسلوك بروتوكولات التوجيه في شبكات MANET مختلفة الحجوم باستخدام برنامج OPNET - حجازية, محمد (Latakia University Journal -Engineering Sciences Series, 2019)
Given the increasing need for information exchange and task sharing in the various domains where computers, mobile communications and wireless networks are used, and with the advent of dynamic ad hoc networks and with the development of a protocol Mobile IP, Building on the electromagnetic mobile field for mobile devices, work has been progressively improved on the mobile networking technology, so in conjunction with the management of multi-hop Ad-hoc network clusters, thus demonstrating the so-called mobile ad hoc networks or MANET networks, which is a shortcut to Mobile Ad-Hoc Network, is a self-configurable wireless network consisting of a mobile contract (mobile phone, laptop,Pad ---), free to move randomly in any direction and with an unspecified topology, and is considered a decentralized independent system. Therefore, the need to work always to improve the work of these networks to achieve the quality of service required according to the specific circumstances of the network [1] [2]. This research examined the specific conditions for the operation of MANET networks according to the size of the network required by the adoption and selection of specific quality service parameters. Therefore, the performance and behavior analysis of some protocols used in different size MANET networks were analyzed by modeling and simulating networks in different numbers of nodes Mobile devices in each network using the Opnet program, according to a number of basic quality service parameters such as Delay, Overload and Throughput to determine optimal cases by choosing the appropriate protocol to help improve the performance of MANET networks by increasing their volumes and number of nodes نظراً للحاجة المتزايدة إلى تبادل المعلومات وتقاسم المهام في المجالات المختلفة التي تُستخدم فيها الحواسيب وأجهزة الاتصالات المتنقلة والشبكات اللاسلكية ومع ظهور شبكات ad hoc الديناميكية ومع تطوير بروتوكول (Mobile IP)، وبالاعتماد على الحقل الكهر طيسي الناشئ للأجهزة المتنقلة، زاد العمل تدريجياً على تحسين تقنية التشبيك للأجهزة المتنقلة وذلك بالتوافق مع إدارة مجموعات شبكة الـ ad hoc متعدد القفزات، وبذلك ظهر ما يسمى بالشبكات اللاسلكية المتنقلة أو ما عُرف اختصاراً بشبكات MANET وهو اختصار لـ (networkN Mobile Ad Hoc) وهي شبكة لاسلكية ذاتية الإعداد وتتألف من عقد متنقلة (هاتف متنقل، حاسب محمول---) حرة التحرك بشكل عشوائي في أي اتجاه وبطوبولوجيا غير محددة، وتعتبر نظام لا مركزي مستقل. ولذلك بقيت الحاجة الى العمل دائماً لتحسين عمل هذه الشبكات بما يحقق جودة الخدمة المطلوبة حسب الظروف المحددة للشبكة[1] [2] تم التطرق في البحث الى تحديد الظروف المناسبة لعمل شبكات MANET وفقاً لحجم الشبكة المطلوب باعتماد واختيار بارامترات جودة خدمة مُحددة ومُناسبة ولذلك تم في هذا البحث تحليل أداء ودراسة سلوك بعض البروتوكولات المستخدمة في شبكات MANET مختلفة الحجوم وذلك عن طريق نمذجة، ومحاكاة سيناريوهات لشبكات بأعداد مختلفة للعقد المتنقلة في كل شبكة باستخدام برنامج Opnet، وذلك وفقاً لعدد من بارامترات جودة الخدمة الأساسية مثل التأخير Delay والحمل Overload والانتاجية Throughput وذلك لتحديد الحالات الامثل باختيار البروتوكول المناسب بما يُساعد في تحسين أداء شبكات MANET حسب تزايد حجومها بزيادة عدد العقد.